Nilpotency of the b ghost in the non-minimal pure spinor formalism - Jusinskas, Renann Lipinski [UNESP] (Springer Nature, 2013)
The b ghost in the non-minimal pure spinor formalism is not a fundamental field. It is based on a complicated chain of operators and proving its nilpotency is nontrivial. Chandia proved this property in arXiv:1008.1778, but with an assumption on the nonminimal variables that is not valid in general. In this work, the b ghost is demonstrated to be nilpotent without this assumption. © 2013 SISSA, Trieste, Italy.
Keywords: Superstrings and Heterotic Strings; Topological Strings